The Effect of Government Spending on the Inclusive Economic Development Index on the Island of Sumatra - Sary, Try Aqnes Novyta; Anggraini, Eka Dewi (Asian Journal of Applied Business and Management, 2024)
This research is motivated by the high economic growth on the island of Sumatra. Sumatra Island has the second largest Gross Domestic Product (GDP) contribution in Indonesia, namely 21.4 percent and the third highest IPEI. This research aims to examine the influence of government spending on economic functions, public services, health and education on the Inclusive Economic Development Index (IPEI). This research uses the Panel Data Regression Method in 10 Provinces on the Island of Sumatra 2016-2023. The research results show that government spending on economic functions and public services has no effect. Meanwhile, Health and Education have a positive and significant influence on IPEI.